CTLs: Killers of intracellular bacteria - Tian, Li; Zhou, Wei; Wu, Xianwei; Hu, Zhuannan; Qiu, Lei; Zhang, Huiyong; Chen, Xue; Zhang, Shaoyan; Lu, Zhenhui (Frontiers in Cellular and Infection Microbiology, 2022)
Many microbial pathogens have evolved a range of capabilities to evade host immune defense mechanisms and to survive and multiply in host cells. The presence of host intracellular bacteria makes it difficult for specific antibodies to function, and cytotoxic T lymphocytes (CTLs) play an important role in eliminating intracellular bacteria. The regulation of key transcription factors can promote CD4+CD8+ T cells to acquire cytolytic ability, and activate multiple pathways to kill intracellular bacteria through the activation signal generated by TCR-CD3 complex transducing TCR to recognize antigens.In this review, we introduce the mechanism of CD4/CD8 CTL differentiation and formation and the ways in which CD4/CD8CTLs kill intracellular bacteria and describe the mechanisms involved in their exertion of effects. In addition, we also introduced their application and prospects in the treatment of bacterial infections.